Evaluating Student Investment Interest Amidst Financial Technology Ease - Astari, Gusti Ayu Shinta Dwi; Wijaya, Bagus Kusuma (PT.KARYA GEMAH RIPAH, 2025)
The emergence of investment features within Fintech ecosystems has democratized access to capital markets for Generation Z. However, empirical evidence suggests a disconnect between accessibility and actual investment participation. This study aims to analyze the gap between investment interest (intention) and actual investment behavior (action) among university students. Employing a descriptive quantitative method with 30 respondents, the research investigates the determinants of low investment uptake despite high digital fluency. The findings reveal a significant